Potencial de Invasão de eucalipto pelas sementes produzidas nos plantios comerciais - Silva, Paulo Henrique Muller da; Poggiani, Fabio; Mori, Edson Seizo [UNESP]; Dias, Carlos Tadeu Santos; Ciero, Luciana Di (My University, 2011)
Over the past few years, the area of planted forests has expanded considerably in Brazil, reaching a level of 6.3 million hectares, which represents approximately 0.7% of the country, mainly with some species of the Eucalyptus genus. However, due to the global concern with biological invasions by exotic species, risk assessment is necessary to evaluate the potential of Eucalyptus species escaping cultivated stands and invading surrounding native ecosystems. Seedlings by natural regeneration from Eucalyptus grandis and E. urophylla, pure and hybrids between the two species were evaluated, by assessing natural regeneration of Eucalyptus in 18 sites located in Brazilian states with plantation forest tradition (Minas Gerais, São Paulo, Rio Grande do Sul and Espírito Santo). Sample plots were installed in the planted stands, along forest roads and in a nearby pasture or native vegetation.,at different distances from the Eucalyptus stands. Regeneration of Eucalyptus was not recorded in 90% of the plots installed outside the eucalipt stands. However, seedlings of eucalypts were observed in 29% of the plots within the commercial stands (mean density of 37 seedlings per hectare) and 40% of the plots located along forest roads (157 seedlings per hectare on average), but no adult plants by natural regeneration were found. The seedlings of eucalypt species studied rarely were found beyond the limits of the cultivated areas. In the planted stands or along forest roads, eucalypts can germinate, but the seedlings apparently do not establish. So the potential for invasion by seeds produced in commercial plantations of Eucalyptus is low.

Durante os últimos anos vem ocorrendo expansão na área das florestas plantadas no Brasil, atingindo o patamar de 6.310.000 hectares, que corresponde a aproximadamente 0,7% do território nacional, com destaque para algumas espécies do gênero Eucalyptus. No entanto, mediante a preocupação global com invasões biológicas por espécies exóticas, faz-se necessária a avaliação do risco de que espécies de eucalipto venham a invadir ecossistemas naturais a partir dos talhões de cultivo. Esta avaliação foi o objetivo do presente estudo, em diferentes regiões, com Eucalyptus grandis, E. urophylla, puros ou híbridos entre as duas espécies. O levantamento foi realizado em 18 áreas, localizadas em diferentes estados brasileiros com tradição florestal (MG, SP, RS e ES), sendo avaliada a regeneração em situações distintas: dentro da área de plantio (talhão), no carreador e em diferentes distâncias do plantio comercial (até 200 m), ocupada por pastagem ou por vegetação nativa. Observou-se que em 90% das parcelas analisadas fora das áreas de cultivo não ocorrem plantas ou plântulas de eucalipto. No entanto, plântulas de eucalipto foram observadas em 29% das parcelas dentro dos talhões comerciais (densidade média de 37 plântulas por hectare) e em 40 % das parcelas localizadas nos carreadores (157 plântulas por hectare, em média), mas não foram observadas plantas adultas oriundas da regeneração natural. Com este levantamento foi verificado que plântulas das espécies de eucalipto estudadas raramente são encontradas fora dos talhões de cultivo. Dentro dos talhões ou nos carreadores as espécies podem germinar, mas aparentemente as plântulas não se estabelecem. Considera-se baixo, portanto, o potencial de invasão pelo eucalipto por meio das sementes produzidas nos plantios comerciais.
Invasive potencial of Eucalyptus species from seeds of commercial stands
Keywords: Risk assessment; Biological invasion; Eucalyptus; Avaliação de risco; Invasões biológicas